Virtual Slicer: Visualizer for Tomographic Medical Images Corresponding Handheld Device to Patient - Shimamura, Sho; Kanegae, Motoko; Morita, Jun; Uema, Yuji; Takahashi, Maiko; Inami, Masahiko; Hayashida, Tetsu; Saito, Hideo; Sugimoto, Maki (International Journal of Virtual Reality, 2015)
This paper introduces an interface that helps understand the correspondence between the patient and medical images. Surgeons determine the extent of resection by using tomographic images such as MRI (Magnetic Resonance Imaging) data. However, understanding the relationship between the patient and tomographic images is difficult. This study aims to visualize the correspondence more intuitively. In this paper, we propose an interactive visualizer for medical images based on the relative position and orientation of the handheld device and the patient. We conducted an experiment to verify the performances of the proposed method and several other methods. In the experiment, the proposed method with a line laser showed the minimum error.